Synergies Between Division of Labor and Gut Microbiomes of Social Insects - Sinotte, Veronica M.; Renelies-Hamilton, Justinn; Taylor, Benjamin A.; Ellegaard, Kirsten M.; Sapountzis, Panagiotis; Vasseur-Cognet, Mireille; Poulsen, Michael (Frontiers in Ecology and Evolution, 2020)
Social insects maximize resource acquisition and allocation through division of labor and associations with microbial symbionts. Colonies divide labor among castes and subcastes, where the plasticity of caste roles decreases in clades with higher social grades. Recent studies indicate that specific castes may also foster distinct gut microbiomes, suggesting synergies between division of labor and symbiosis. The social organization of a colony potentially partitions evolutionary persistent microbial partners to optimize symbioses and complement division of labor. However, research in this area has received limited attention. To elucidate if a structured microbiota is adaptive, we present three testable predictions to address consistent community structure, beneficial functions, and selection for microbiota that support caste roles. First, we posit that social insect groups spanning lower to higher social grades exhibit increasingly distinct caste microbiomes, suggesting that structured microbiomes may have evolved in parallel to social complexity. Second, we contend that the development of these microbiomes during colony maturation may clarify the extent to which they support division of labor. Third, we predict that mature social insect colonies with the most extreme division of labor demonstrate the strongest distinctions between caste microbiomes, carrying the greatest promise of insight into microbiome composition and function. Ultimately, we hypothesize that caste-specific microbiomes may enhance symbiotic benefits and the efficiency of division of labor, consequently maximizing fitness.